Effective distribution of gold nanorods in ordered thick mesoporous silica: a choice of noninvasive theranostics - Prasad, Rajendra; Selvaraj, Kaliaperumal (ACS Applied Materials & Interfaces, 2023)
Porous silica coated gold nanorod core-shell structures demonstrate a multifunctional role in bioimaging, drug delivery, and cancer therapeutics applications. Here, we address a new approach for effective distribution of gold nanorods (GNRs) in a mesoporous silica (MS) shell, viz., one nanorod in one silica particle (GMS). We have studied that silica coating presents major advantages for the better biocompatibility and stability of GNRs. In this study, two different thicknesses of silica shell over GNRs have been discussed as per the application's need; GNRs in thin silica (11 nm) are fit for phototherapy and bioimaging, whereas thick and porous silica (51 nm) coated gold nanorods are suitable for triggered drug delivery and theranostics. However, effective distribution of GNRs in ordered architecture of thick mesoporous silica (MS, more than 50 nm thickness) with high surface area (more than 1000 m(2)/g) is not well understood so far. Here, we present methodical investigations for uniform and highly ordered mesoporous silica coating over GNRs with tunable thickness (6 to 51 nm). Judicious identification and optimization of different reaction parameters like concentrations of silica precursor (TEOS, 1.85-43.9 mM), template (CTAB, 0.9-5.7 mM), effect of temperature, pH (8.6-10.8), stirring speed (100-400 rpm), and, most importantly, the mode of addition of TEOS with GNRs have been discussed. Studies with thick, porous silica coated GNRs simplify the highest ever reported surface area (1100 m(2)/g) and cargo capacity (57%) with better product yield (g/batch). First and foremost, we report a highly scalable (more than 500 mL) and rapid direct deposition of an ordered MS shell around GNRs. These engineered core-shell nanoparticles demonstrate X-ray contrast property, synergistic photothermal-chemotherapeutics, and imaging of tumor cell (96% cell death) due to released fluorescent anticancer drug molecules and photothermal effect (52 degree celsius) of embedded GNRs. A deeper insight into their influence on the architectural features and superior theranostics performances has been illustrated in detail. Hence, these findings indicate the potential impact of individual GMS for image guided combination therapeutics of cancer.
Keywords: CombinationTherapy; Contrast Agent; Core-ShellStructure; GoldNanorods; Imaging; Mesoporous silica; Nanoparticles; TheranosticsIntervention